2012
DOI: 10.1096/fj.12-215491
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of RASSF1A gene promoter is regulated by p53 and DAXX

Abstract: Inactivation of the tumor suppressor Ras-association domain family 1 isoform A (RASSF1A) due to epigenetic silencing occurs in a variety of human cancers, and still largely unknown are the regulators and mechanisms underlying RASSF1A gene promoter methylation. Herein, we report that this methylation is regulated by p53 and death-associated protein 6 (DAXX) in acute lymphoblastic leukemia (ALL). We found that p53 bound to the RASSF1A promoter, recruiting DAXX as well as DNA methyltransferase 1 (DNMT1) for DNA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…It was shown recently that RASSF1A promoter methylation is regulated by p53 and deathassociated protein 6 (DAXX) [151]. The authors have found that p53 binds to the RASSF1A promoter, recruits DAXX and DNMT1, leading to DNA methylation and subsequently to inactivation of RASSF1A.…”
Section: Thementioning
confidence: 99%
See 1 more Smart Citation
“…It was shown recently that RASSF1A promoter methylation is regulated by p53 and deathassociated protein 6 (DAXX) [151]. The authors have found that p53 binds to the RASSF1A promoter, recruits DAXX and DNMT1, leading to DNA methylation and subsequently to inactivation of RASSF1A.…”
Section: Thementioning
confidence: 99%
“…Interestingly, fluctuation in p53 protein levels did not affect the rates of RASSF1A methylation. Conversely, methylation of the RASSF1A promoter was critically controlled by DAXX, as the enforced overexpression of DAXX led to enhanced RASSF1A promoter methylation, whereas inhibition of DAXX reduced RASS-F1A methylation [151].…”
Section: Thementioning
confidence: 99%
“…On the other hand, DAXX regulates transcription of mammalian and viral genes via its ability to interact with a number of transcription factors [for more details see (Preston and Nicholl, 2006; Saffert and Kalejta, 2006; Salomoni and Khelifi, 2006; Lindsay et al, 2008; Lukashchuk and Everett, 2010; Tsai et al, 2011; Rivera-Molina et al, 2012; Glass and Everett, 2013; Schreiner et al, 2013; Shalginskikh et al, 2013)] and epigenetic regulators. In particular, DAXX interacts with HDAC-II (Hollenbach et al, 2002), acetyltransferases (CBP) (Kuo et al, 2005), and DNA methyltransferase (Dnmt1) (Puto and Reed, 2008; Zhang et al, 2013), suggesting an important role in chromatin remodeling.…”
Section: The Pml-interacting Protein Daxx Is a Chaperone For The Histmentioning
confidence: 99%
“…The RASSF1 gene encodes several isoforms, including RASSF1A , RASSF1B , and RASSF1C , all of which are generated from alternative mRNA splicing and promoter usage[15]. RASSF1A transcriptional silencing is frequently observed feature in multiple types of cancer as a result of promoter hypermethylation; however, few reports are available describing the mechanisms underlying this phenomenon[1619]. RASSF1A transcription is suppressed by hypermethylation in breast, ovarian, gastric, nasopharyngeal, and bladder cancers as well as neuroblastoma and renal cell lines[2025].…”
Section: Introductionmentioning
confidence: 99%